An empirical study of alcoholic consumption and labor productivity in Japan - Masayo Sato; Yasushi Ohkusa (Osaka University, Institute of Social and Economic Research (ISER), 2003)
This paper examines the relationship between labor productivity and alcohol consumption based on research conducted with a limited sample of workers who drink alcohol. Estimation results show that in the case of males, the amount of alcohol consumed significantly raises labor productivity, with an elasticity of approximately 0.13. In females, we cannot reach the firm conclusion. Conversely, the reverse relationship between labor productivity and alcohol consumption cannot be confirmed. Moreover, an awareness of appropriate alcohol consumption supports the sixth strategy of the Health Japan 21 policy, which is to reduce national alcohol consumption by about 20%.
Keywords: I12; I18; J31; 330; Alcoholic Consumption; Labor Productivity; Addiction; Income Effect; Health Promotion Policy; Health Japan 21; Policy Evaluation; Alkoholkonsum; Arbeitsproduktivität; Gesundheitspolitik; Schätzung; Japan